CROSS-SECTIONAL, QUESTIONNAIRE-BASED SURVEY ON PRIMARY PREVENTION ATITUDES AMONG ROMANIAN TEENAGERS - Catalina Iulia Saveanu; Danila Oana; Alexandru Iovan; Daniela Anistoroaei; Octavian Boronia; Alexandra Ecaterina Saveanu (Romanian Society of Oral Rehabilitation, 2023)
(1) Background: Evidence from studies indicate that oral health behaviors, such as eating habits and oral hygiene methods, are in close connection with the occurence of oro-dental disseases. Teenagers behave not only through their own choices, motivations, experience, lifestyle, beliefs and value system but they are conditioned by sociocultural norms. Obtaining data from teenagers could be esential to influence the development of oral health care policies. The purpose of this study was to evaluate the level of health education among teenagers by knowledge regarding the use of: fluoride based products, oro-dental hygiene, food hygiene, the level of stress correlated with the visit to the dental office. (2) Methods: A questionnaire was developed and the purpose was to investigate the level of health education among teenagers. The questionnaire was applied online, it included 25 questions, with unique answers. (3) Results: The result of the study showed that the average age of the studied group was 18.24 (±0.428) with a minimum age of 18 years old and a maximum of 19 years old, 58.9% (103) female subjects and 41.1% (72) male, 61.1% (107) from urban areas and 38.6% (68) from rural areas. Based on the analysis of the results, the following opinion was obtained: the majority of responses were predominantly from females. However, this does not diminish the interest and caution with which male subjects approach personal hygiene. Particularly, the majority of responses were from urban residents. Regarding oral hygiene, adolescents have knowledge of proper oral hygiene methods such as tooth brushing, mouthwash, and dental floss. (4) Conclusions: Teenagers make a connection between their own health and that of others, recognizing that by taking care of their health, they can protect their loved ones.